STUDI KOMPARATIF PERFORMA MOTOR HONDA WIN 100 DENGAN PENGGUNAAN GROUND STRAP KABEL KOIL DAN VARIASI BUSI BERBEDA - Irvan Ainur (POLITALA PRESS, 2025)
A method to improve engine performance on the ignition coil is the addition of a ground strap to the coil cable and the selection of the right type of spark plug. The ground strap functions to stabilize the electric current from the coil and allows for a larger and more stable spark plug. The study aims to determine the effect of using a coil cable ground strap and spark plug variations on the performance of the Honda Win 100. The spark plugs used are standard, iridum and platinum spark plugs. Testing was carried out using a Dyno test tool and a Honda Win 100 motorcycle. The first step is to test all types of spark plugs with standard coil cables, then all types of spark plugs are tested with ground strap coil cables. The test results show that iridium spark plugs with standard coil cables have the highest torque value compared to other variations and iridium spark plugs with ground strap coil cables have the highest power value compared to other variations. From the test results, the use of ground straps does not have much effect on changes in motorcycle power and torque.